Gain modulation and odor concentration invariance in early olfactory networks - Marachlian, Emiliano (2023)
The broad receptive field of the olfactory receptorsconstitutes the basis of a combinatorial code that allows animals to detect anddiscriminate many more odorants than the actual number of receptor types thatthey express. One drawback is that high odor concentrations recruit loweraffinity receptors which can lead to the perception of qualitatively differentodors. Here we addressed the contribution thatsignal-processing in the antennal lobe makes to reduce concentration dependencein odor representation. By means of calcium imaging and pharmacologicalapproach we describe the contribution that GABA receptors play in terms of theamplitude and temporal profiles of the signals that convey odor informationfrom the antennal lobes to higher brain centers. We found that GABA reduces theamplitude of odor elicited signals and the number of glomeruli that are recruitedin an odor-concentration-dependent manner. Blocking GABA receptors decreasesthe correlation among glomerular activity patterns elicited by differentconcentrations of the same odor. In addition, we built a realistic mathematicalmodel of the antennal lobe that was used to test the viability of the proposedmechanisms and to evaluate the processing properties of the AL network underconditions that cannot be achieved in physiology experiments. Interestingly,even though based on a rather simple topology and cell interactions solelymediated by GABAergic lateral inhibitions, the AL model reproduced key featuresof the AL response upon different odor concentrations and provides plausiblesolutions for concentration invariant recognition of odors by artificialsensors.